PELESTARIAN TRADISI UANG JIMPITAN DI LINGKUNGANDUSUNNGEPUH LOR, DESA BANYUSIDI, PAKIS, MAGELANG,JAWA TENGAH - Muhammad Hasyim (UII, 2014)
Jimpitan is one attempt to hold capital for community activities such as garbagefees, street lights and various other shared dues. Nowadays, the burden of dues in largequantities each month maybe commuted to implement the program jimpitan where theamount and timing mechanisms whose contributions can be tailored to the needs ofsociety. Jimpitan can be either money or rice which shows the tradition of ruralcommunities that continue to uphold mutual cooperation, togetherness and helping eachother. Jimpitan creation program in the Ngepuh Lor village run smoothly, along with theenthusiasm of citizens who participate in the program.